Aplikasi Android Untuk Berbagai Jenis Toko Secara Online - Chandra Ari Gunawan; Julianti Kasih (Maranatha University Press, 2016)
E-Commerce as an alternative mean of transaction along with the usage of smartphone as a tool to perform e-commerce transaction is gaining ground. This development could be seen from the emergence of numerous mobile payment applications.The usage of mobile devices to pay for goods, services, bills, or money transfer.Stores as a location for transaction are currently in a fierce completion to gain customers, on the other hand, there are issues for the customers, the customers often do not have adequate information, the distance to the store is too far, or not enough time to visit the store. Those are the reasons that drive the author to create an application to resolve the aforementioned issues.An application to list various types of online store in a mobile app.The stores registered in the app could provide information regarding the store location, products that the stores offered, ongoing promotion, and contact for shipment of information about the store’s products. The user as the customer could see the list of stores according to the type of store selected, could see the information that is provided by the store, and perform purchasing transaction on the selected store. Keywords — e-commerce, mobile, online, smartphone, stores